Protective effect of chondroitin sulfate nano-selenium on chondrocyte of patients with Kashin-Beck disease. (May 2021) - Qiao, Lichun; Amhare, Abebe F; Deng, Huan; Lv, Yizhen; Zhao, Yan; Liu, Jiaxin; Lei, Jian; Wang, Liyun; Chilufya, Mumba M; Han, Jing
Objective: To investigate the protective effect of chondroitin sulfate nano-selenium (SeCS) on chondrocyte of Kashin-Beck disease (KBD). Methods: Chondrocyte samples were isolated from the cartilage of three male KBD patients (54–57 years old). The chondrocytes were respectively divided into four groups: (a) control group, (b) SeCS supplement group (100 ng/mL SeCS), (c) T-2 + SeCS supplement group (20 ng/mL T-2 + 100 ng/mL SeCS), and (d) T-2 group (20 ng/mL T-2). Live/dead staining and transmission electron microscopy (TEM) were used to observe cell viability and ultrastructural changes in chondrocytes respectively. Expressions of Caspase-9, cytochrome C (Cyt-C), and chondroitin sulfate (CS) structure-modifying sulfotransferases including carbohydrate sulfotransferase 3, 15 (CHST-3, CHST-15), and uronyl 2-O-sulfotransferase (UST) were examined by quantitative real-time polymerase chain reaction. Results: After one- or three-days intervention, the number of living chondrocytes in the SeCS supplement group was higher than that in the control group, while it is opposite in the T-2 + SeCS supplement group and T-2 group. The cellular villi number in the surface increased in the SeCS supplement group compared with the control group. Mitochondrial morphology density was improved in the T-2 + SeCS supplement group compared with the T-2 group. Expressions of CHST-3, CHST-15, UST, Caspase-9, and Cyt-C on the mRNA level significantly increased in the T-2 + SeCS supplement group and T-2 group compared with the control group. Conclusions: SeCS supplement increased the number of living chondrocytes, improved the ultrastructure, and altered the expressions of CS structure-modifying sulfotransferases, Caspase-9, and Cyt-C.